ADP-glucose transport by the chloroplast adenylate translocator is linked to starch biosynthesis - Pozueta-Romero, J. (1991)
In organello starch biosynthesis was studied using intact chloroplasts isolated from spinach leaves (Spinacia oleracea). Immunoblot analysis using a specific antiserum against the mitochondrial adenylate (ADP/ATP) translocator of Neurospora crassa shows the presence of an adenylate translocator protein in the chloroplast envelope membranes, similar to that existing in mitochondria and amyloplasts from cultured cells of sycamore (Acer pseudoplatanus). The double silicone oil layer-filtering centrifugation technique was employed to study the kinetic properties of adenylate transport in the purified chloroplasts; ATP, ADP, AMP, and most importantly ADP-Glc were shown to be recognized by the adenylate translocator. Similar to the situation with sycamore amyloplasts, only ATP and ADP-Glc uptake was inhibited by carboxyatractyloside, an inhibitor of the mitochondrial adenylate translocator. Evidence is presented to show that the ADP-Glc transported into the chloroplast stroma is utilized for starch synthesis catalyzed by starch synthase (ADP-Glc: 1,4-α-d-glucan 4-α-d-glucosyltransferase). The high activity of sucrose synthase producing ADP-Glc observed in the extrachloroplastic fractions suggests that starch biosynthesis in chloroplasts may be coupled with the direct import of ADP-Glc from the cytosol.